Patient-prosthesis mismatch in patients treated with transcatheter aortic valve implantation – predictors, incidence and impact on clinical efficacy. A preliminary study - Zbroński, Karol; Rymuza, Bartosz; Scisło, Piotr; Grodecki, Kajetan; Dobkowska, Paulina; Wawrzacz, Marek; Wilimski, Radosław; Słowikowska, Anna; Kochman, Janusz; Filipiak, Krzysztof J.; Opolski, Grzegorz; Huczek, Zenon (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2017)
Introduction : Patient-prosthesis mismatch (PPM) is relatively frequent after surgical aortic valve replacement (SAVR) and negatively impacts prognosis. Aim : We sought to determine the frequency and clinical effects of PPM after transcatheter aortic valve implantation (TAVI). Material and methods : Overall, 238 patients who underwent TAVI were screened. Moderate PPM was defined as indexed effective orifice area (EOAi) between 0.65 and 0.85 cm2/m2, and severe PPM as < 0.65 cm2/m2. All-cause mortality and the Valve Academic Research Consortium 2 (VARC-2) defined composite of clinical efficacy at 1 year were the primary endpoints. Results : Finally, 201 patients were included (mean age: 79.6 ±7.4 years, 52% females). The femoral artery served as the delivery route in 79% and most of the prostheses were self-expanding (68%). Any PPM was present in 48 (24%) subjects, and only 7 (3.5%) had severe PPM. Body surface area (BSA) independently predicted any PPM (OR = 16.9, p 20 mm Hg. Conclusions : Severe PPM after TAVI is rare, can be predicted by larger BSA and does not seem to affect mid-term mortality or composite clinical outcome. Larger studies are needed to find different independent predictors of PPM and elucidate its impact in terms of device durability and long-term clinical efficacy.